Exultemur et laetemur. Riscritture inglesi e angloamericane della storia di Cristo - Paola Di Gennaro (Between, 2016)
The novel genre has explored – with its peculiar possibilities – the dynamic changes, in significance and expectations, that the figure of Christ, a “character” strictly codified in the Gospels,  has inspired again and again in different contexts. The starting point is the examination of constants and variants in the representation of Christ in the discourse developed in the period that stretches from the last decades of the nineteenth century to the end of the last century (Renan, Wallace, Papini, Mauriac, D. H. Lawrence, Moore, Graves, Kazantzakis, Artaud, Moorcock, Bulgakov, Endō, Saramago) – rewritings that have reinterpreted historical and religious facts in order to transform them into something else: epitome, metaphor, objective correlative, scapegoat. The aim of this paper is to analyse a number of British and Anglo-American literary texts and films of the last decades which have used irony or explicit laughter as instruments for retelling in heterodox – but only apparently blasphemous – ways the life of Jesus, between canonical and apocryphal Gospels, making it new material, euphoric and vital hypostasis. This was possible only after the appearance of Nietzsche’s antichrist, after the figure of Christ had become, in the nineteenth century, Hegelian (Strauss), proto-communist (Sauriac and Lynn Linton) and positivist (Renan). In particular, two texts will be analyzed: The Gospel According to Biff, Christ’s Childhood Pal (2002), by Christopher Moore, and The Second Coming (2011) by John Niven, and also classic films such as Monty Python’s Life of Brian (1979), and Dogma (1999), directed by Kevin Smith. In these works of the twenty-first century, Christ is still a character who has to fulfil his destiny, in one way or another; these texts represent real theological fictions, complex constructions that want to draw, in an effective way, a reassuring road to salvation, a customised paradise.